(untitled) (CSIAM Transactions on Applied Mathematics, 2020)
In this work, we introduce a fast numerical algorithm to solve the time-dependent radiative transport equation (RTE). Our method uses the integral formulation of RTE and applies the treecode algorithm to reduce the computational complexity from O(M2+1/d) to O(M1+1/dlogM), where M is the number of points in the physical domain. The error analysis is presented and numerical experiments are performed to validate our algorithm.